EVALUATION OF RADIATION DOSES USING A DAP METER DURING VARIOUS MEDICAL IMAGING PROCEDURES IN A TERTIARY HEALTHCARE HOSPITAL - AJAY PRAJAPATI; VIJAY KUMAR SRIVASTAVA; ARUN CHOUGULE; POOJA SHARMA; DESH DEEPAK SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study is to evaluate dose reference levels (DRLs) to provide quality images with minimal radiation dose to patients during the X-ray examination by employing the as low as reasonably achievable principle (as low as reasonably achievable). Methods: The DRLs were measured with a dose area product (DAP) meter (KERMAX-Plus SDP, model 120–210), and data were compared with other studies. The local DRL values were calculated at 75 % of the mean DAP value. Results: The measured minimum DRL value for hand-anterior to posterior examination was 0.04 Gy.cm2 and for routine chest-posterior to anterior view, it was 0.59 Gy.cm2 in this study. The maximum measured DRL value was 2.75 Gy.cm2 for lumbar spine lateral radiography, but this was also much lower than other reported studies. Conclusion: The DAP meter provides a reliable estimation of DRLs values and assists in the optimization of radiation dose, without compromising image quality during the X-ray examination practice in a radiology department.